Unveiling miR-1468-5p: A New Prognostic Biomarker and Therapeutic Target in Lung Adenocarcinoma - Chen, Yi; Li, Dongbing; Fang, Yueyu (Recent Patents on Anti-Cancer Drug Discovery, 2025)
BackgroundmiR-1468-5p, a type of microRNA, is acknowledged for its crucial involvement in a variety of cancerous processes. Nonetheless, the specific impact of this microRNA on lung adenocarcinoma (LUAD) has not yet been clearly defined.ObjectiveOur aim was to investigate how miR-1468-5p influences LUAD.MethodsThe Cancer Genome Atlas (TCGA) offered specimens for our research. Employing statistical techniques, we assessed the diagnostic and prognostic significance of miR-1468-5p, as well as its association with clinical characteristics. Our analysis delved into the target genes and the regulatory mechanisms influenced by miR-1468-5p. The expression levels of miR-1468-5p in LUAD cell lines were validated through quantitative reverse transcription polymerase chain reaction (qRT-PCR).ResultsThe expression of miR-1468-5p varied significantly across different cancer types. The presence of reduced miR-1468-5p levels was correlated with a lower likelihood of overall survival in LUAD patients, with a statistically significant result (p = 0.005). miR-1468-5p demonstrated independent prognostic significance in LUAD and potentially contributes to disease progression via multiple pathways, including the HIF-1 signaling pathway and more. There was a significant reduction in miR-1468-5p expression in LUAD cell lines when compared to cells of the normal lung epithelium.ConclusionmiR-1468-5p may serve as a useful patent as a therapeutic intervention target and a prognostic indicator for LUAD patients.
Keywords: therapeutic target